Good governance and rule of law - Nik Mahmod, Nik Ahmad Kamal (2013)
Good governance is basically governing in the right and just ways. Good governance relates to good administration at both public and private sectors. Corporate governance is synonymous and the common usage in the private sector. Common characteristics of good governance include transparency, accountability, participatory and rule of law. Rule of law is the focus of this paper. The principle in itself is problematic because of multifarious interpretation Nonetheless, the consensus has been that rule of law is essential in any government and breach of its principles may lead to arbitrariness and breach of fundamental rights. The paper will expound the roles of rule of law in ensuring good governance and how abuse of power and corruption have undermined rule of law seriously and subsequently affect good governance.